Hamlet [videorecording (DVD)] - Colleran, Bill; Gielgud, John, 1904-2000; Burton, Richard, 1925-1984; Drake, Alfred, 1914-1992; Cronyn, Hume; Herlie, Eileen; Redfield, William, 1927-1976; Rose, George, 1920-1988; Voskovec, Jiří, 1905-1981; Shakespeare, William, 1564-1616 (Image Entertainment, 1999)
Staged in rehearsal room and modern dress conditions, this is Richard Burton's performance as Hamlet. This play opened on Broadway April 9, 1964. This recording is not derived from a film, but from an attempt to simply record the stage show for one cinematic showing by placing cameras in the stalls during an actual performance.